Engaging the Egyptian diaspora for development: Egyptian government policy and knowledge transfer - Iman, Dawood (AUC Knowledge Fountain, 2014)
Viewed within the context of an increasingly transnational world, diasporas have become crucial development actors for their respective home countries contributing to the transfer of essential financial, social, and human capital. The level and impact of diasporic contributions to homeland development have been found to depend on multiple variables, of which perhaps most relevant to policy makers in developing countries, is government policy towards emigration in general and the diaspora in specific. Although Egypt has a sizable diaspora with a relatively high skill level, the potential of its diaspora seems unrealized especially in regards to the role it could play in transferring essential skills, knowledge, and expertise to Egypt. Hence, this thesis examines Egypt's emigration and diaspora policy in an effort to determine whether or not Egyptian government policies, in both formulation and implementation, are conducive towards diaspora engagement in general and knowledge transfer in specific. Using Alan Gamlen's concept of transnational governmentality and his impending policy typology, this thesis first examines Egypt's diaspora engagement policies and then examines Egypt's knowledge transfer programs. Egyptian policy documents are analyzed and interviews with Egyptian policymakers, former government officials, and experts are conducted and analyzed.